Fabrication of Functional bioMOF-100 Prototype as Drug Delivery System for Breast Cancer Therapy - Alves, Renata Carolina [UNESP]; Perosa Fernandes, Richard; Lira de Farias, Renan; da Silva, Patricia Bento; Santos Faria, Raquel; Quijia, Christian Rafael [UNESP]; Galvão Frem, Regina Célia [UNESP]; Azevedo, Ricardo Bentes; Chorilli, Marlus [UNESP] (MDPI, 2022)
Breast cancer is the most frequent cause of cancer death in women, representing the fifth leading cause of cancer death overall. Therefore, the growing search for the development of new treatments for breast cancer has been developed lately as well as drug delivery systems such as biocompatible metal–organic Frameworks (bio-MOFs). These may be promising and attractive for drug incorporation and release. The present study aims to develop a drug carrier system RCA (bioMOF-100 submitted to the activation process) containing incorporated curcumin (CCM), whose material surface is coated with folic acid molecules (FA) to promote the targeting of drug carrier systems to the tumor region. They were synthesized and characterized using several characterization techniques. The materials were submitted to drug encapsulation tests, whose encapsulation efficiency was 32.80% for CCM@RCA-1D. Using the 1H nuclear magnetic resonance (NMR) spectroscopy technique, it was possible to verify the appearance of signals referring to folic acid, suggesting success in the functionalization of these matrices. In vitro tests such as cell viability and type of cell death were evaluated in both series of compounds (CCM@RCA-1D, CCM@RCA-1D/FA) in breast tumor lines. The results revealed low toxicity of the materials and cell death by late apoptosis. Thus, these results indicate that the matrices studied can be promising carriers in the treatment of breast cancer.
Keywords: bio-MOFs; cancer; curcumin; delivery systems; functionalization